Pelatihan pembuatan biochar sebagai sumber nutrisi bagi tanaman di greenhouse Universitas Sulawesi Barat: Training in making biochar as a source of nutrition for plants at the Greenhouse of the Universitas Sulawesi Barat - St. Kurniah; Maruf Maruf; Resti Patricia; Ones Sule; Abd. Rukman Burhan (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2024)
Environmental pollution in Indonesia, such as agricultural waste such as rice husks, corn cobs, and coconut shells, often accumulates on unused land, causing environmental pollution. Biochar can be used to process waste while increasing soil fertility. This practice aims to evaluate biochar production from rice husks and its benefits. This activity involved students and teaching assistants at the Green House of the Faculty of Agriculture and Forestry, West Sulawesi University. The pyrolysis process burns rice husks in low oxygen conditions to produce biochar, and its benefits will be tested. The study showed that rice husk biochar improves soil structure and fertility, increases water retention, and provides a habitat for beneficial microorganisms. Biochar increases fertilizer use efficiency and effectively contributes to reducing agricultural production costs. Adding biochar to the soil can increase the availability of nutrients such as major cations, phosphorus, and nitrogen, reduce fertilizer loss through leaching and evaporation, and reduce negative impacts on plant growth and soil health. Therefore, rice husk biochar is a potential soil conditioner that can increase the fertility and productivity of agricultural land. Biochar has porous properties and a large surface area that allows it to absorb and retain water, nutrients, and beneficial microorganisms. Applying biochar to agricultural land reduces biomass waste, increases crop yields, and reduces soil and water pollution due to fertilizer leaching. Therefore, rice husk biochar provides a sustainable solution for agricultural waste management and soil quality improvement.